Business management strategies for MSMEs Melati Cake's - Prasetya, Prita; Trixie, Angie; Wijaya, Francisco Redi; Dewi, Gusti Ayu Saras Ayu Pagar; Dharma, Jeremy; Aurielle, Nakeisha; Angela, Shierly; Soen, Stanley; Hwa, Theng Kiem; Santoso, Viona (Priviet Social Sciences Journal, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are essential in employing the community to improve the economy and productivity. Kuningan Village is a village whose residents run many MSME businesses. Partners still need help improving their business development, especially in operational, digital marketing, and financial aspects. Universitas Prasetiya Mulya has supported groups in the Community Development program to assist partners in developing their businesses. The group has re-branded logo packaging and provided education on digital marketing to reach potential customers on a larger scale. Second, improvements have been made to cash flow recording so that all financial flows are more controlled. Third, equipment purchases, business licensing realization, and SOP implementation have been done. With group assistance, partners have succeeded in increasing sales profits, increasing awareness of potential customers, increasing productivity, and making partners adaptable to technological developments.